Two walls versus three wall orbital decompression for thyroid eye disease: A systematic review and meta-analysis - Haissan Iftikhar; Deewani, Muhammad Hammad; Abbas, Syed Akbar; Lassi, Zohra; Jai Das; Shahzada Ahmed (Journal of the Pakistan Medical Association, 2025)
Objective: To assess whether three-wall surgical orbital decompression confers any benefit over two-wall surgical orbital decompression in terms of decrease in proptosis and new-onset diplopia. Method: The systematic review was conducted in 2020, and comprised literature search on Elton B. Stephens Co, Cumulative Index to Nursing and Allied Health Literature, Wiley Cochrane Library, Web of Science and PubMed databases for studies published from 1948 to 2019 that compared two-wall (medial and inferior) endoscopic decompressions with three-wall decompression. Relevant data was extracted from the literature, and was subjected to qualitative assessment using Cochrane Effective Practice and Organisation of Care criterion by two researchers independently. Results: Of the 111 studies identified, 2(1.8%) met the eligibility criteria, with a total of 72 patients. Of them, 37(51.4%) patients had undergone two-wall decompression and 35(48.6%) had undergone three-wall decompression. There was significant difference seen with change in proptosis in the groups in favour of three-wall decompression (p=0.0003). New onset diplopia showed a greater trend towards two-wall decompression, but not significantly (p=0.39). Conclusion: Limited evidence was found to determine if three-wall orbital decompression is superior to two-wall orbital decompression for thyroid eye disease. Key Words: Thyroid-associated ophthalmopathies, Thyroid eye disease, Grave’s ophthalmopathy.